1996
DOI: 10.1111/j.1365-2044.1996.tb14997.x
|View full text |Cite
|
Sign up to set email alerts
|

A double‐blind comparison of codeine and morphine for postoperative analgesia following intracranial surgery

Abstract: SummaryCodeine and morphine were compared in a double-blind studv of postoperative analgesia in 40 patients afrer intracranial neurosurger.r. Eighteen patients received codeine phosphate 60 nig and 18 morphine sulphate 10 mg, both by intramuscular injection; 4 patients (10%) required no analgesia. Both drugs provided analgesia within 20 min of injection but morphine was more efectirw than codeine beyond 60min ( p = 0.01). Fewer doses of morphine than codeine were required (j = 0.003). Nine patients requested o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(39 citation statements)
references
References 11 publications
1
38
0
Order By: Relevance
“…3,[6][7][8] Codeine is widely used on our neurosurgical ward and although the 75% overall prevalence of moderate to severe pain is within the 60 to 84% reported by others, 1-3 the present study certainly reinforces the concern that a more potent analgesic needs to be used in this surgical population.…”
Section: Discussionsupporting
confidence: 56%
“…3,[6][7][8] Codeine is widely used on our neurosurgical ward and although the 75% overall prevalence of moderate to severe pain is within the 60 to 84% reported by others, 1-3 the present study certainly reinforces the concern that a more potent analgesic needs to be used in this surgical population.…”
Section: Discussionsupporting
confidence: 56%
“…This finding was unexpected. Goldsack et al [14], who compared the change in P a CO 2 20-120 min after intramuscular morphine or codeine, and Tanskanen et al [19], who studied paracetamol and ketoprofen as adjuncts to an oxycodone PCA in 45 patients, found similar mean changes but a smaller standard deviation in the measured P a CO 2 . In our study we found two patients who had changes in P a CO 2 that were noticeably greater than the changes in the other patients.…”
Section: Discussionmentioning
confidence: 97%
“…Ten percent of the population demethylate less than 0.5% of a dose of codeine, resulting in no analgesic effect, and many others metabolise < 15%. Goldsack and colleagues demonstrated that better analgesia can be achieved using morphine than codeine given by the intramuscular route [14]. Tramadol has been available in the UK since 1994 and has the advantage of a dual mechanism of analgesia, being both an agonist at opioid receptors and activating monoaminergic spinal inhibition of pain transmission.…”
mentioning
confidence: 99%
“…Morphine was also more effective than codeine following craniotomy; this was found for IM prn administration of both compounds (Goldsack et al, 1996 Level II) but also in a comparison of PCA morphine with IM codeine (Sudheer et al, 2007 Level II). PCA fentanyl was more effective than prn IV fentanyl and did not increase the risk of adverse effects after craniotomy (Morad et al, 2009 Level II).…”
Section: Opioidsmentioning
confidence: 90%